On dark and bloody ground : an oral history of the West Virginia mine wars. - Lawrence, Anne T. (West Virginia University Press, 2021)
"Oral histories with participants in and observers of the Battle of Blair Mountain and other Appalachian mine wars of the 1920s and 1930s, supplemented with introductory material, maps, and photographs"--